DESIGN AND ANALYSIS OF ALUMINIUM ADHESIVE JOINTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Adhesive bonding is widely used for sheet metal joining. Majority of automobile, aerospace parts, mainly their body components are joined together by different types of adhesives. So their growing demand needs the detailed study of strength analysis of adhesive joints. Investigation on single lap adhesive joint is to be done for various applications. Overlap length, load and Adhesive layer thickness has to be varied in the defined range & analysis is done by to see the nature of changes in the joint. FE analysis is done by using Ansys to observe the nature of changes in the joint. Validation by Mechanical testing is done by using Universal Testing Machine up to ultimate limit. Overall joint strength is related to maximum force that can be sustained by joint. The overlap at which the maximum force is required to break the joint is the length which can considered as optimum adhesive overlap length